2003
DOI: 10.1002/glia.10333
|View full text |Cite
|
Sign up to set email alerts
|

Focal astrocyte loss is followed by microvascular damage, with subsequent repair of the blood‐brain barrier in the apparent absence of direct astrocytic contact

Abstract: Blood-brain barrier (BBB) breakdown is a feature of cerebral ischaemia, multiple sclerosis, and other neurodegenerative diseases, yet the relationship between astrocytes and the BBB integrity remains unclear. We present a simple in vivo model in which primary astrocyte loss is followed by microvascular damage, using the metabolic toxin 3-chloropropanediol (S-alpha-chlorohydrin). This model is uncomplicated by trauma, ischaemia, or primary immune involvement, permitting the study of the role of astrocytes in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
113
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 55 publications
20
113
0
Order By: Relevance
“…In these experiments, we also showed that the BBB dysfunction occurred concurrently with the earliest morphologic evidence of astrocyte death. Two potential explanations could account for these findings: (1) astrocyte death could induce dysfunction of the BBB, which has been shown in other models 11,52 or (2) the BBB dysfunction itself could induce damage to astrocytes. The second hypothesis is not supported by other models of BBB damage including osmotic disruption by mannitol infusion or stroke, where no astrocyte death occurs despite a dramatic BBB rupture.…”
Section: Discussionmentioning
confidence: 67%
“…In these experiments, we also showed that the BBB dysfunction occurred concurrently with the earliest morphologic evidence of astrocyte death. Two potential explanations could account for these findings: (1) astrocyte death could induce dysfunction of the BBB, which has been shown in other models 11,52 or (2) the BBB dysfunction itself could induce damage to astrocytes. The second hypothesis is not supported by other models of BBB damage including osmotic disruption by mannitol infusion or stroke, where no astrocyte death occurs despite a dramatic BBB rupture.…”
Section: Discussionmentioning
confidence: 67%
“…Cultured cells derived from newborn SHRSPs indicated astrocytic dysfunction in these animals (Yamagata et al, 1997). Astrocytes are important components of the BBB that support endothelial cells (Abbott et al, 2006), and astrocytic degeneration induces microvascular damage and greatly increases the permeability of the BBB (Willis and et al, 2004). Therefore, in SHRSPs, astrocytes may not function adequately to support the functioning of the BBB, and this may partly contribute to the high incidence of DND in these animals, because the permeability of the BBB in SHRSPs increased greatly due to 2-VO at 6 and 24 h after ischemia-reperfusion (Abraham et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant glial cells in the central nervous system (Abbott, 2002;Goudstein and Betz, 1986) are the astrocytes, covering 90% of the cerebrovascular surface (Willis et al, 2004). These cells participate in the regulation of free neurotransmitters, immune response, repair of the extracellular matrix, control of the cerebrovascular barrier and trophic support (Eddleston and Mucke, 1993).…”
Section: Introductionmentioning
confidence: 99%